Fluoride Removal in Synthetic Drinking Water by Electrocoagulation Using Aluminum Electrodes - Sedou, Moudassirou; Mande, Seyf-Laye Alfa-Sika; Sanou, Yacouba; Arouna, Kadidja (European Journal of Applied Sciences, 2022)
Fluoride is recognized as an essential constituent in the human diet. Low fluoride concentration could prevent dental problem while higher fluoride concentration will cause dental and skeletal fluorosis. This study aimed to remove fluoride in synthetic drinking water by electrochemical system. It had been performed at laboratory scale using fluoride synthetic water. The process consisted to optimize the fluoride removal in drinking water using the Aluminum electrodes. The effects of operating conditions such as the initial ion fluoride concentration, current density or intensity, contact time, and NaCl amount were studied. Experimental results showed that with the initial concentration of 15 mg/L using the optimal intensity (1.5 A), an admitted residual concentration (1.5 mg/L) was observed during 45 min of electrolysis while maximum fluoride removal percentage of 100 % was achieved for 60 min. The variation of energy consumption from 1.18 to 22.35 Wh showed that the electrocoagulation can be applied using photovoltaic energy for fluoride treatment in drinking water.